The Relationship between Knowledge about Anesthesia Procedures and the Anxiety of Patients Who Will Undergo Surgery at RSUD Raden Mattaher Jambi - Tianingsih Tianingsih; Mara Imam Taufiq Siregar; Huntari Harahap; Andy Hutariyus; Budi Justitia (International Journal of Health and Social Behavior, 2026)
Background: Preoperative anxiety is a common response to perceived physical and psychological threats that may affect hemodynamic stability, increase postoperative pain, prolong hospitalization, and even lead to surgery cancellation. Limited knowledge of anesthesia procedures is considered an important contributing factor because inadequate information can increase fear and unpreparedness before surgery. Methods: This cross-sectional study involved 126 patients undergoing elective surgery at Raden Mattaher Regional General Hospital, Jambi. Respondents were selected based on the criteria of age ≥18 years, ASA physical status I–II, literacy, and willingness to participate. Data on anesthesia-related knowledge and preoperative anxiety were collected using structured questionnaires. The relationship between variables was analyzed using the Kolmogorov–Smirnov test because the assumptions for the Chi-square test were not fulfilled. Results: Most respondents were aged 51–60 years, had completed senior high school, were employed, had no previous surgical experience, presented with hypertension, and had normal pulse rates. Moderate knowledge (48.4%) and moderate anxiety (48.2%) were the most common findings. Statistical analysis demonstrated a significant association between knowledge of anesthesia procedures and preoperative anxiety (p = 0.0001). Conclusion: Improving patients' knowledge through comprehensive preoperative education may reduce anxiety, enhance readiness, and support physiological stability before elective surgery.